2 Answers | Add Yours
I suppose the * means composition of function.
Similarly (f *g)(x) = f(g(x)).
If that is the case, we replace the x on f(x) by 2x - 1.
`(f * g)(x) = f(g(x)) = 3(2x - 1)^2 - 4`
Use foil method on (2x - 1)^2 = (2x - 1)(2x - 1).
`(f * g)(x) = 3(4x^2 - 4x + 1) - 4`
Use Ditributive Property.
`(f * g)(x) = 12x^2 - 12x + 3 - 4`
Hence, final answer will be:
(f * g)(x) = 12x^2 - 12x - 1
`f(x)=3x^2-4` `g(x)= 2x-1`
Note that product isn't abelian indeed:
`f[g(x)] != g[f(x)]`
We’ve answered 319,639 questions. We can answer yours, too.Ask a question